การลดข้อบกพร่องของสภาพรถภายนอกสำหรับระบบการขนส่งรถยนต์ - วีรวิชญ์ อัครจิรไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To reduce the exterior defect of the vehicle during transportation system by using Failure Mode and Effect Analysis (FMEA) technique concept to analyze for the quality factors. The defect modes were identified and prioritized by studying the mainly occurrence of defect location and using the Pareto diagram. The selection of mainly defect types were chosen by considering Pareto diagram weighting with each defect severity based on repairing cost in order to collect the defect type from the damage cost. The cause and effect diagram were used to analyze the mainly causes and apply the technique of Failure Mode and Effect Analysis (FMEA) to evaluate 3 factors : the severity, the occurrence and the detective of each cause and were calculated the risk priority number(RPN). The selection of defects improvement were considered the high level of severity and using the Pareto diagram of RPN (80% RPN accumulation). The improvement results showed that 1. The average of defect rate was reduced from 834 PPM to 367 PPM per month. 2. The damage value of repairing was decreased from 492,495 baht to 64,857 baht per month 3. The value of Risk Priority Number was reduced from 33.3% to 92.8% compared with before improvement.